Development and Verification of Fire Service Area Re-division and Fire Fighter Deployment Methodologies using Census Spatial Data - Lee, Ji-Soo; Lee, oon-Ha; Seo, Hyun-cheol; Hong, Won-Hwa (International Journal of Engineering and Technology, 2018)
The South Korean fire service force deployment criteria have insufficient considerations compared to the US, the UK, and Japan, and even when compared with OECD countries, the national criteria for fire service forces should be improved. In particular, the criteria for division of fire service areas are concentrated on administrative districts so that the response times of actual front line fire houses cannot but be much different among regions. In addition, since the numbers of residents under each fire fighter’s charge show larger differences among lower organizations, technical methodologies to respond to such differences should be urgently developed. Therefore, in this study, fire service areas were redivided based on accessibility utilizing census polygon data andÂ fire fighters were reorganized using the population attribute information embedded in the data. The methodology presented in this study was applied to the target area to quantitatively evaluate the degrees to which the differences in the numbers of residents under one fire fighter’s charge and the accessibility were improved. Â